Immediate results after vacuum drainage endoscopic treatment in patients with full esophageal wall defects - P. A. Kulish; A. Y. Popov; V. A. Porhanov; A. G. Baryshev; V. G. Slavinsky; A. L. Kovalenko; M. I. Bykov; I. Y. Sholin; V. V. Chaykin (Инновационная медицина Кубани, 2019)
We performed the first analysis of our clinical experience with endoscopic vacuum drainage in 10 patients with esophageal wall defects complicated by mediastinitis or peritonitis. We define this method efficiency to arrest local inflammatory process, it occurred possible to preserve impaired esophagus regardless the time of injury and this fact guarantees patient’s life quality management. Furthermore, while performing reconstructive interventions in cases with improved inflammations we could reduce of local and common complication development.